Impending thyroid storm in a pregnant woman with undiagnosed hyperthyroidism: A case report and literature review. Issue 3 (January 2018) - Ma, Yushan; Li, Hao; Liu, Jin; Lin, Xuemei; Liu, Hui
Abstract: Rationale: Thyroid storm is a rare complication during caesarean section of patients with hyperthyroidism. It occurs abruptly, with a high mortality rate if not recognized immediately and aggressively treated. Herein, we reported a case of impending thyroid storm during a caesarean section. Patient concerns: A healthy 23-year-old woman with undiagnosed hyperthyroidism underwent an emergency caesarean section under general anesthesia. After tracheal extubation, the patient exhibited abnormal tachycardia, agitation, sweating, and hyperpyrexia. Diagnoses: The clinical manifestation and the following thyroid function test indicate a high index of suspicion for impending thyroid storm. Interventions: Hydrocortisone and esmolol were intravenously administered immediately. Propylthiouracil and propranolol were orally administered after the patient regained complete consciousness. Outcomes: Due to our immediate recognition and aggressive treatment, more serious manifestations of thyroid storm were avoided. Lessons: Good antenatal care is very important for pregnant women, and they should be generally screened for thyroid disorders, especially if the resting heart rate is >100 beats/min and weight increases are inconsistent with gestational age. When hyperthyroidism is suspected, drugs that excite the sympathetic nerves or promote the release of histamine should not be used during caesarean section.